TINGKAT KEPATUHAN ODHA MINUM OBAT ARV DI POLI VCT MUTU MANIKAM RSUD DR H MOCH ANSARI SALEH BANJARMASIN - Erna Prihandiwati; Novia Ariani; Yudi Hardi Susilo (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Acquired Immunodeficiency Syndrome (AIDS ) is a collection of symptoms of a disease caused by the Human Immunodeficiency Virus (HIV) which damages the body's immunity. People With HIV AIDS (PLWHA) should undergo therapy Antiretroviral (ARV) drugs for life. Provionce was ranked 23 out of 34 provinsi in Indonesia with HIV / AIDS cases are as much as 2,274 cases. This study aims to determine the level of adherence of PLWHA taking ARV drugs in Mutu Manikam VCT Ward Dr. H. Moch Ansari Saleh Banjarmasin as well the relationship of the level of vulnerability with the characteristics of respondents. This study uses a cross-sectional design that is prospective with consecutive sampling techniques . Samples that met the inclusion and exclusion criteria were 109 PLWHA. Data is collected with the distribution of MARS questionnaires. Statistical analysis used was cross tabulation analysis with Pearson Chi Square correlation test. The results of the study showed that the level of adherence of PLWHA taking ARV drugs with a high level of adherence was 75 PLWHA (69%), the level of adherence was 34 PLWHA (31%). There was no significant correlation between adherence to taking ARV drugs with the demographic characteristics of respondents with p > 0.05 . Based on this study it was concluded that PLWHA in Mutu Manikam VCT Ward Dr. H. Moch Ansari Saleh Hospital Banjarmasin has a high level of adherence taking ARV drugs. The relationship between the level of adherence with characteristics of respondents (gender, age, education, occupation, length of treatment and comorbidities) in this study was not statistically significant.